SCREEN TIME ON WEEKDAY AND WEEKEND AMONG HEALTH COLLEGE STUDENTS AND THE CORRELATION TO NUTRITIONAL STATUS - Farapti, Farapti; Puspasari, Devi; Astutik, Erni; Fadilla, Chusnul; Nurul Ratna Mutu Manikam (The Indonesian Journal of Public Health, 2025)
Introduction: The prevalence of obesity in Indonesia reached 21.8% in 2018 and increased by 6.4% compared to 2013. Low physical activity is known as a risk factor of obesity. College students’ activities are closely related to use of screen time. Aims: To identify the activities of screen time for assignments and non-assignments on weekdays and weekends among college student and analyze its relationship with body mass index (BMI).  Methods: This study was conducted in 2018 with a cross sectional design among undergraduate students at the Faculty of Public Health, Universitas Airlangga, Indonesia, conducted in 2018. The screen time questionnaire was adapted from Sedentary Behavior Questionnaire. The correlation between screen time duration and BMI was analysed by Spearman test. Results: The female subjects were dominant (81.1%) and 28.4% of subjects as overweight-obese. The screen time duration in non-assignment activity on weekends has a positive correlation with the nutritional status of health college students (p 0.000, r 0.49), particularly duration of social networking sites and listening to music were more significant in obese than normal. The use of smartphones takes a high part, approximately 4 hours 20 minutes both on weekdays and on weekends. Conclusion: The screen time duration in non-assignment activity on weekend was associated to nutritional status of health college students. Health college students are encouraged to reduce screen time for non-assignment activities on weekends and to use wisely several smartphone applications or social networking sites to control body weight and achieve a balanced nutritional status.